The Effectiveness of Using the Frayer Model to Improve The Understanding of Arabic Vocabulary in Class VIII Students at MTs Muhammadiyah Pekanbaru - Husnah, Qomariyatul; Masrun, Masrun; Agustiar, Agustiar (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2024)
This research is an experimental research that aims to determine the effectiveness of the model (Frayer) to improve Arabic language learning outcomes in class VIII MTs Muhammadiyah 02 Pekanbaru. The formulation of the problem in this study is: Is the Model (Frayer) effective in improving Arabic Vocabulary Mastery of Class VIII Students of MTs in Muhammadiyah 02 Pekanbaru? This research begins with designing learning steps, implementation, observation, then testing. The population of the study was class VIII students at MTs Muhammadiyah 02 Pekanbaru with samples of class VIII A and VIII B students. The subjects of the study were Arabic teachers and students of class VIII A and VIII B. The instruments used to collect data in this study consisted of observation and tests. From the analysis of the data obtained, it can be concluded that the Model (Frayer) can improve Arabic language learning outcomes in class VIII MTs Muhammadiyah 02 Pekanbaru very effectively. Based on the results of the student post-test, it shows that with a value of to = 6.779 which is greater than tt at a significance level of 1% = 2.001 and a significance level of 5% = 1.671, Ho is rejected and Ha is accepted. The class that uses the Model (Frayer) with an average of 84.93% is very good (Jayyid Jiddan). There fore, implementing the Model (Frayer) has a strong effect on student learning outcomes.